Seismic Performance and Retrofit Evaluation of an Existing Pile-Wharf Structure - Erdogan, Hakan; Doran, Bilge; Seckin, Aytug; Akbas, Bulent; Celikoglu, Yesim; Bostan, Tuba (ASCE-AMER SOC CIVIL ENGINEERS, 2017)
Pile-wharf structures are one of the substantial facilities for marine transportation along the shorelines. Due to their logistical significance, keeping the pile-wharf structures operational under all circumstances is crucial. Seismic forces are one of the major threats that can disrupt the functionality of the pile-wharf structures. This paper focuses on the seismic evaluation and upgrade of an existing wharf structure in Turkey by using the performance-based evaluation principles of a displacement-based design approach. According to the insufficient seismic performance of the existing wharf structure, two retrofitting schemes were proposed that considered the practicality and cost-efficiency aspects. In both schemes, additional piles were used to withstand the seismic demands, eliminate the torsional irregularity, and increase the lateral stiffness of the structure. The key differences between the proposed retrofitting schemes were the numbers and layout patterns of the additional piles. The numbers of additional piles used in the first and second schemes were 18 and 15, respectively. This study indicates that the performance-based evaluation of wharf structures using a displacement-based design approach provides a thorough understanding of the nonlinear behavior of marine structures and that the addition of piles is a reliable method for improving the seismic performance of pile-wharf structures. (C) 2017 American Society of Civil Engineers.
Keywords: Pile-wharf structures; Performance-based design; Seismic retrofitting; BEHAVIOR; Construction & Building Technology; Engineering